Periodontal Outcome after Surgical Exposure of Bucally Impacted Maxillary Canine - Abid Kanju, Taimur Khan, Syeda Sahar Ali, Munawar Manzoor Ali, Adeel Babar But, Samar Nazir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Many clinicians refer to the maxillary and mandibular canines as the "cornerstone" of the arch, and when they are in their ideal position, they are essential in providing a well-balanced occlusal scheme that supports dentofacial balance, harmony, stability, and neuromuscular and functional stability. Objective: This study examined the variations in periodontal health characteristics between palatally impacted maxillary canines (PIMC) and buccally impacted maxillary canines (BIMC) following open method surgical-orthodontic therapy. Methods: Total 30 patients were presented in this study. Patients were divided in two groups, group A had 15 patients with unilateral BIMC and group B with unilateral PIMC among 15 patients. A year following surgical-orthodontic therapy, the keratinized tissue and probing depth were measured, and the differences between the two sides were examined. Results: The BIMC group showed considerably lower keratinized tissue values for canines than for the untreated side (P = 0.004) and significantly larger probing depths for lateral incisors than for the untreated side (P = 0.032). In the PIMC group, no discernible variations were found. Conclusion: Using an open approach for surgical-orthodontic therapy, we found that in BIMC, the treated tooth lost its periodontal keratinized tissue, and the surrounding lateral incisors lost their periodontal connection. Keywords: BIMC, PIMC, keratinized tissue